Heteropolyacid compound-phosphonate liquid flame retardant as well as preparation method and application thereof

By developing a heteropolyacid compound - phosphonate liquid flame retardant, the problem of flammability of fiber-reinforced epoxy resin composites is solved, and the effects of high flame retardant, low heat release and low smoke release are achieved, which are suitable for areas with high flame retardant performance requirements.

CN119823445AActive Publication Date: 2025-04-15CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510110527.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The existing fiber-reinforced epoxy resin composites have insufficient flame retardant properties due to their highly flammable organic matrix, which limits their application in the fields of high flame retardant performance requirements.

Method used

A heteropolyacid compound - phosphonate liquid flame retardant is developed, which is formed by reacting phosphomolybdate or transition metal phosphomolybdate with a liquid phosphorus-based flame retardant, with good compatibility and exhibits high flame retardant, low heat release and low smoke release properties in resin composite materials.

Benefits of technology

This liquid flame retardant significantly improves the flame retardant performance of carbon fiber reinforced epoxy resin composite materials, reduces the peak heat release rate, total heat release and smoke release, meets the requirements of low smoke and low heat release, and maintains the mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005256548680000021
    Figure BDA0005256548680000021
  • Figure BDA0005256548680000041
    Figure BDA0005256548680000041
  • Figure BDA0005256548680000071
    Figure BDA0005256548680000071
Patent Text Reader

Abstract

The invention belongs to the technical field of materials, and particularly relates to a heteropolyacid compound-phosphonate liquid flame retardant as well as a preparation method and application thereof. Compared with the prior art, the heteropolyacid compound-phosphonate liquid flame retardant provided by the invention is added into resin, so that the resin has excellent flame retardant property and meets the requirements of low smoke and low heat release amount, when the temperature around a resin composite material is rapidly increased, phosphomolybdate ions promote rapid dehydration and carbonization of a resin matrix, and the flame retardant property of the resin composite material is improved. In a condensed phase, phosphomolybdate ions participate in a catalytic carbonization reaction, and when the ambient temperature of the composite material is rapidly increased, the liquid phosphorus-based flame retardant is decomposed to release PO. And P. free radicals, and high-energy HO. And H. in a gas phase can be effectively captured to inhibit a free radical reaction; besides, after the liquid phosphorus-based flame retardant is decomposed, a part of phosphorus element is retained in a condensed phase in the form of phosphate, and phosphate particles are uniformly dispersed in a carbon layer, so that the oxidation resistance and the barrier effect of the carbon layer are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material technology, and in particular relates to a heteropolyacid compound-phosphonate liquid flame retardant, a preparation method and application thereof. Background Art

[0002] Fiber reinforced polymer materials have attracted extensive attention due to their excellent properties such as high specific strength, high specific stiffness, chemical resistance and corrosion resistance. With the rapid development and increasing demand for lightweight structures and materials, fiber reinforced polymer materials can replace traditional materials such as aluminum, steel and concrete used in high-performance engineering structures, and are gradually used in various fields such as machinery manufacturing, automobiles (such as McLaren MP4 and BMW i8), aerospace engineering (such as Airbus A350 and Boeing 787) and civil engineering. In commercial aircraft, 80% to 90% of the internal structure is made of fiber reinforced polymer materials. However, compared with metal structural materials, the main disadvantage of fiber reinforced polymer materials (including composites prepared from renewable resources) is their highly flammable organic matrix, such as epoxy resin composites, which are easily ignited and the flame spreads violently after ignition, which largely limits the application of epoxy resin and its related composites, especially in some fields with high flame retardant requirements.

[0003] At present, the most common strategy for constructing flame-retardant carbon fiber reinforced epoxy resin composites is to add non-reactive flame retardant additives (red phosphorus, ammonium phosphate, aluminum hydroxide, intumescent, zinc-based and boron-based flame retardants, etc.) to the epoxy resin matrix. The advantage of this method is that flame retardants are widely available and have a large operating space, but most flame retardants are in solid form and are incompatible with epoxy resins, which will inevitably lead to a decrease in the mechanical properties of the composites. In addition, the addition of flame retardants often causes an increase in the viscosity of the epoxy resin, resulting in the inability of the resin to fully impregnate the carbon fibers and change the composite molding process. In addition, in the resin transfer molding (RTM) process, solid flame retardants will also be unevenly distributed due to the filtering effect of the carbon fibers, resulting in uneven flame retardant properties.

[0004] Therefore, in order not to affect the properties of carbon fiber itself and to improve the flame retardant properties of carbon fiber reinforced epoxy resin composites while maintaining their mechanical properties, it is crucial to develop an efficient liquid flame retardant with good compatibility with the epoxy resin matrix. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a heteropolyacid compound-phosphonate liquid flame retardant, a preparation method and application thereof, wherein the heteropolyacid compound-phosphonate liquid flame retardant has good compatibility with the resin matrix and has the properties of high flame retardancy, low heat release and low smoke release.

[0006] The present invention provides a heteropolyacid compound-phosphonate liquid flame retardant, which is formed by the reaction of a first flame retardant and a second flame retardant; the first flame retardant is selected from phosphomolybdic acid and / or transition metal phosphomolybdate; the second flame retardant is a liquid phosphorus-based flame retardant; the mass ratio of the first flame retardant to the second flame retardant is (0.5-6): (9.5-4).

[0007] Preferably, the second flame retardant has a structure shown in formula (I):

[0008]

[0009] Wherein, R1 and R2 are each independently selected from a C1-C10 alkyl group or a C6-C20 aryl group;

[0010] R3 is selected from C1-C20 alkyl, C1-C20 hydroxyalkyl, C1-C20 alkoxy or C6-C20 aryloxy.

[0011] Preferably, the second flame retardant is selected from one or more of dimethyl methylphosphonate, dimethyl octadecylphosphonate, dimethyl 2-(hydroxyethyl) phosphate, tributyl phosphonate and triphenyl phosphonate.

[0012] Preferably, the first flame retardant is selected from one or more of phosphomolybdic acid, copper phosphomolybdate, nickel phosphomolybdate and chromium phosphomolybdate.

[0013] Preferably, the reaction temperature is greater than room temperature; and the reaction time is 1 to 6 hours.

[0014] The present invention also provides a method for preparing the above-mentioned heteropolyacid compound-phosphonate liquid flame retardant, comprising the following steps:

[0015] The first flame retardant and the second flame retardant are mixed and reacted to obtain a heteropolyacid compound-phosphonate liquid flame retardant.

[0016] The present invention also provides a resin composition, comprising a resin and the above-mentioned heteropolyacid compound-phosphonate liquid flame retardant.

[0017] Preferably, the mass ratio of the resin to the heteropolyacid compound-phosphonate liquid flame retardant is (95-85):(5-15).

[0018] Preferably, the resin is selected from epoxy resin; and the resin composition further comprises an amine curing agent.

[0019] The present invention also provides a flame retardant material, comprising the above heteropolyacid compound-phosphonate liquid flame retardant or the above resin composition.

[0020] The present invention provides a heteropolyacid compound-phosphonate liquid flame retardant, which is formed by the reaction of a first flame retardant and a second flame retardant; the first flame retardant is selected from phosphomolybdic acid and / or transition metal phosphomolybdate; the second flame retardant is a liquid phosphorus-based flame retardant; the mass ratio of the first flame retardant to the second flame retardant is (0.5-6): (9.5-4). Compared with the prior art, the heteropolyacid compound-phosphonate liquid flame retardant provided by the present invention is added to the resin to enable the resin to have excellent flame retardant properties and meet the requirements of low smoke and low heat release. When the temperature around the resin composite material rises rapidly, the phosphomolybdate ions promote the rapid dehydration and carbonization of the resin matrix. In the condensed phase, the phosphomolybdate ions participate in the catalytic carbonization reaction. For the liquid phosphorus-based flame retardant, when the temperature around the composite material rises rapidly, the liquid phosphorus-based flame retardant decomposes to release PO· and P· free radicals. These PO· and P· can effectively capture high-energy HO· and H· in the gas phase, thereby inhibiting free radical reactions. In addition, after the liquid phosphorus-based flame retardant is decomposed, a portion of the phosphorus element is retained in the condensed phase in the form of phosphate, and these phosphate particles are evenly dispersed in the carbon layer, which is beneficial to improving the antioxidant capacity and barrier effect of the carbon layer.

[0021] Experiments show that adding 10wt% of heteropolyacid compound-phosphonate liquid flame retardant to carbon fiber reinforced epoxy resin composite materials can reduce the peak heat release rate by more than 40%, the total heat release by more than 38%, and the total smoke release by more than 47%. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A synthetic route for the heteropolyacid compound-phosphonate liquid flame retardant provided by the present invention;

[0023] Figure 2 This is a verification diagram of the existence form of phosphomolybdic acid in the heteropolyacid compound-phosphate ester liquid flame retardant obtained in Example 4 of the present invention. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] The present invention provides a heteropolyacid compound-phosphonate liquid flame retardant, which is formed by the reaction of a first flame retardant and a second flame retardant; the first flame retardant is phosphomolybdic acid and / or transition metal phosphomolybdate; the second flame retardant is a liquid phosphorus-based flame retardant; the mass ratio of the first flame retardant to the second flame retardant is (0.5-6):(9.5-4).

[0026] In a specific embodiment provided by the present invention, the first flame retardant is preferably one or more of phosphomolybdic acid, copper phosphomolybdate, nickel phosphomolybdate and chromium phosphomolybdate.

[0027] In a specific embodiment provided by the present invention, the transition metal phosphomolybdate is preferably prepared according to the following steps: mixing a transition metal hydroxide and phosphomolybdic acid in water, heating the reaction, and removing the solvent to obtain a transition metal phosphomolybdic acid; the molar ratio of the transition metal hydroxide to the phosphomolybdic acid is preferably 3:1; the temperature of the heating reaction is preferably 50°C to 70°C, more preferably 55°C to 65°C, and more preferably 60°C; the time of the heating reaction is preferably 3 to 6 hours; after the heating reaction, it is preferably filtered to remove impurities and then remove the solvent; the method for removing the solvent is a method well known to those skilled in the art and is not particularly limited. In the present invention, it is preferably vacuum drying after rotary evaporation; the temperature of the vacuum drying is preferably 60°C to 90°C, more preferably 70°C to 90°C, and more preferably 80°C; the time of the vacuum drying is preferably 10 to 15 hours, and more preferably 12 hours.

[0028] In a specific embodiment provided by the present invention, the second flame retardant has a structure shown in formula (I), wherein R1 and R2 are each independently preferably a C1-C10 alkyl group or a C6-C20 aryl group, more preferably a C1-C8 alkyl group or a C6-C10 aryl group, further preferably a C1-C5 alkyl group or a C6-C10 aryl group, and most preferably a C1-C4 alkyl group or a phenyl group; R3 is preferably a C1-C20 alkyl group, a C1-C20 hydroxyalkyl group, a C The present invention relates to an alkyl group selected from the group consisting of C1-C20 alkoxy and C6-C20 aryloxy, more preferably an alkyl group consisting of C1-C18, a hydroxyalkyl group consisting of C1-C10, an alkoxy group consisting of C1-C10 or a aryloxy group consisting of C6-C10, further preferably an alkyl group consisting of C1-C18, a hydroxyalkyl group consisting of C1-C5, an alkoxy group consisting of C1-C5 or a aryloxy group consisting of C6-C10, and most preferably an alkyl group consisting of C1-C18, a hydroxyalkyl group consisting of C1-C2, an alkoxy group consisting of C1-C4 or a aryloxy group consisting of C6-C10.

[0029]

[0030] In a specific embodiment provided by the present invention, the second flame retardant is preferably one or more of dimethyl methylphosphonate, dimethyl octadecylphosphonate, 2-(hydroxyethyl) dimethyl phosphate, tributyl phosphonate and triphenyl phosphonate.

[0031] In a specific embodiment provided by the present invention, optionally, the mass ratio of the first flame retardant to the second flame retardant is 0.5:9.5, 1:9, 1.5:8.5, 2:8, 2.5:7.5, 3:7, 3.5:6.5, 4:6, 4.5:5.5, 5:5, 5.5:4.5, 6:4 or a range between any two of the above ratios.

[0032] In a specific embodiment provided by the present invention, when the first flame retardant is a transition metal phosphomolybdate, the mass ratio of the first flame retardant to the second flame retardant is (0.5-1):(9.5-9).

[0033] In a specific embodiment provided by the present invention, the reaction temperature is preferably greater than or equal to room temperature.

[0034] In a specific embodiment provided by the present invention, the reaction time is 1 to 6 hours; optionally, the reaction time is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours or a range between any two of the above values.

[0035] The heteropolyacid compound-phosphonate liquid flame retardant provided by the present invention is added to a resin so that the resin has excellent flame retardant properties and meets the requirements of low smoke and low heat release. When the temperature around the resin composite material rises rapidly, the phosphomolybdate ions promote the rapid dehydration and carbonization of the resin matrix. In the condensed phase, the phosphomolybdate ions participate in the catalytic carbonization reaction. For the liquid phosphorus-based flame retardant, when the temperature around the composite material rises rapidly, the liquid phosphorus-based flame retardant decomposes to release PO· and P· free radicals. These PO· and P· can effectively capture high-energy HO· and H· in the gas phase, thereby inhibiting free radical reactions. In addition, after the liquid phosphorus-based flame retardant is decomposed, a portion of the phosphorus element is retained in the condensed phase in the form of phosphate, and these phosphate particles are evenly dispersed in the carbon layer, which is beneficial to improving the antioxidant capacity and barrier effect of the carbon layer.

[0036] The present invention also provides a method for preparing the heteropolyacid compound-phosphonate liquid flame retardant, comprising the following steps: mixing a first flame retardant and a second flame retardant to obtain the heteropolyacid compound-phosphonate liquid flame retardant.

[0037] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.

[0038] In a specific embodiment provided by the present invention, the temperature of the mixing reaction is preferably greater than or equal to room temperature.

[0039] In a specific embodiment provided by the present invention, the mixing reaction time is preferably 1 to 6 hours; optionally, the mixing reaction time is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours or a range between any two of the above values.

[0040] In a specific embodiment provided by the present invention, the mixing method can be any method well known to those skilled in the art without any particular limitation. In the present invention, stirring and / or ultrasound is preferred.

[0041] In a specific embodiment provided by the present invention, the mixing method is preferably ultrasound; the power of the ultrasound is preferably 50-200W, more preferably 80-150W, further preferably 80-120W, and most preferably 100W.

[0042] The present invention also provides a resin composition, comprising a resin and the above-mentioned heteropolyacid compound-phosphonate liquid flame retardant.

[0043] In a specific embodiment provided by the present invention, the resin is preferably an epoxy resin, more preferably one or more of bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin. When the temperature around the epoxy resin composite material rises rapidly, the phosphomolybdate ions promote the rapid dehydration and carbonization of the epoxy resin matrix. In the condensed phase, the phosphomolybdate ions participate in the catalytic carbonization reaction, and cooperate with the liquid phosphorus flame retardant to promote the further cross-linking of diketones and oxygen-containing heterocyclic phenols formed during the decomposition of the epoxy resin (EP) into carbon.

[0044] In a specific embodiment provided by the present invention, the mass ratio of the resin to the heteropolyacid compound-phosphonate liquid flame retardant is preferably (95-85):(5-15); optionally, the mass ratio of the resin to the heteropolyacid compound-phosphonate liquid flame retardant is 95:5, 92:8, 90:10, 88:12, 85:15 or a range between any two of the above ratios.

[0045] In a specific embodiment provided by the present invention, the resin composition further includes an amine curing agent; the amine curing agent is any amine curing agent well known to those skilled in the art, without any special restrictions, and is preferably one or more of divinyltriamine, trivinyltetramine, polyetheramine, meta-phenylenediamine, meta-xylene diamine, 4,4'-diaminodiphenylmethane, trimethylhexanediamine, diaminodiphenyl sulfone, menthane diamine, dicyclohexylmethane diamine, isophorone diamine, polyamide, imidazole, 2-methylimidazole, 1-aminoethyl-2-methylimidazole, 1-cyanoethyl substituted imidazole, polyamide, linear phenolic resin and dicyandiamide.

[0046] In a specific embodiment provided by the present invention, the mass ratio of the resin to the amine curing agent is 100:(1-40); optionally, the mass ratio of the resin to the amine curing agent is 100:1, 100:5, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40 or a range between any two of the above ratios.

[0047] In a specific embodiment provided by the present invention, the resin composition preferably further comprises a fiber reinforcement material; the fiber reinforcement material can be a fiber reinforcement material well known to those skilled in the art, without any special limitation, and in the present invention, preferably one or more of carbon fiber, glass fiber and basalt fiber. In this case, the resin composition is a fiber-reinforced resin composite material, wherein the percentage of the resin is generally related to the surface density of the fiber reinforcement material, and generally the content of the resin is between 30% and 40%.

[0048] In a specific embodiment provided by the present invention, the resin composition is prepared according to the following method: a resin is mixed with a heteropolyacid compound-phosphonate liquid flame retardant for a first time, and then a molten amine curing agent is added for a second mixing, ultrasonic dispersion, defoaming treatment, and curing to obtain a resin composition; the first mixing time is preferably 10 to 60 minutes, more preferably 20 to 40 minutes, and more preferably 30 minutes; the second mixing time is preferably 10 to 60 minutes, more preferably 20 to 40 minutes, and more preferably 30 minutes; the ultrasonic dispersion temperature is preferably 50°C to 70°C, more preferably 55°C to 65°C, and more preferably 60°C; the ultrasonic dispersion time is preferably 10 to 60 minutes, more preferably 20 to 40 minutes, and more preferably 30 minutes; the defoaming treatment is preferably vacuum defoaming; the curing is preferably cured at 100°C for 2 hours and at 160°C for 3 hours.

[0049] The present invention also provides a flame retardant material, comprising the above heteropolyacid compound-phosphonate liquid flame retardant or the above resin composition.

[0050] In a specific embodiment provided by the present invention, the flame retardant material can be applied to electrical components, glass fiber composites, carbon fiber composites, basalt fiber composites, mixed fiber composite printed circuit boards, cables or electronic chemical materials and parts, etc., which have high requirements on the flame retardant properties of the materials.

[0051] In order to further illustrate the present invention, a heteropolyacid compound-phosphonate liquid flame retardant provided by the present invention, a preparation method thereof and applications are described in detail below in conjunction with examples.

[0052] The reagents used in the following examples are all commercially available; some of the raw materials and their sources are shown in Table 1.

[0053] Table 1 Sources of some raw materials

[0054]

[0055]

[0056] Example 1: PM 0.5 MP 9.5 Preparation (PMA:DMMP mass ratio = 0.5:9.5)

[0057] Take 2.5 g of PMA and 47.5 g of DMMP (PMA:DMMP=0.5:9.5), dissolve PMA directly in DMMP, and ultrasonicate at 100 watts for 1 hour at room temperature until PMA is completely dissolved in DMMP to obtain a dark green transparent liquid, which is a heteropolyacid compound-phosphonate liquid flame retardant (PM 0.5 MP 9.5 ), the synthetic route is shown in Figure 1 .

[0058] Example 2: Preparation of PM1MP9 (PMA:DMMP mass ratio = 1:9)

[0059] Take 5 g of PMA and 45 g of DMMP (PMA:DMMP=1:9), dissolve PMA directly in DMMP, and perform ultrasound at 100 watts for 1 hour at room temperature. PMA is completely dissolved in DMMP to obtain a dark green transparent liquid, which is a heteropolyacid compound-phosphonate liquid flame retardant (PM1MP9). The synthesis route is shown in Figure 1 .

[0060] Example 3: Preparation of PM2MP8 (PMA:DMMP mass ratio = 2:8)

[0061] Take 10 g of PMA and 40 g of DMMP (PMA:DMMP=2:8), dissolve PMA directly in DMMP, and ultrasonicate at 100 watts for 1 hour at room temperature. PMA is completely dissolved in DMMP to obtain a dark green transparent liquid, which is a heteropolyacid compound-phosphonic acid lipid liquid flame retardant (PM2MP8). The synthesis route is shown in Figure 1 .

[0062] Example 4: Preparation of PM4MP6 (PMA:DMMP mass ratio = 4:6)

[0063] Take 20 grams of PMA and 30 grams of DMMP (PMA:DMMP=4:6), dissolve PMA directly in DMMP, and ultrasonicate at 100 watts for 1 hour at room temperature. PMA is completely dissolved in DMMP to obtain a dark green transparent liquid, which is a heteropolyacid compound-phosphonate liquid flame retardant (PM4MP6). The synthesis route is shown in Figure 1 .

[0064] The reactivity of phosphomolybdate ions with imidazole was used to verify the existence of phosphomolybdate ions in DMMP. A small amount of imidazole was directly added to the synthesized PM4MP6, and a yellow precipitate was immediately generated in the dark green transparent liquid, proving that the phosphomolybdate in PM4MP6 does exist in an ionic state.

[0065] When imidazole is added to the dark green transparent liquid obtained in Example 4, a precipitate is produced, as shown in FIG. Figure 2 As shown, it is shown that phosphomolybdic acid exists in the dark green transparent liquid in the form of ions.

[0066] Example 5: Preparation of PM5MP5 (PMA:DMMP mass ratio = 5:5)

[0067] Take 25 grams of PMA and 25 grams of DMMP (PMA:DMMP=5:5), dissolve PMA directly in DMMP, and ultrasonicate at 100 watts for 1 hour at room temperature. PMA is completely dissolved in DMMP to obtain a dark green transparent liquid, which is a heteropolyacid-phosphonate liquid flame retardant (PM5MP5). The synthesis route is shown in Figure 1 .

[0068] Example 6: Preparation of PM6MP4 (PMA:DMMP mass ratio = 6:4)

[0069] Take 30 g of PMA and 20 g of DMMP (PMA:DMMP=5:5), dissolve PMA directly in DMMP, and perform ultrasound at 100 watts for 1 hour at room temperature. PMA is completely dissolved in DMMP to obtain a dark green transparent liquid, which is a heteropolyacid compound-phosphonate liquid flame retardant (PM6MP4). The synthesis route is shown in Figure 1 .

[0070] Example 7: Preparation of PMMPNi (Ni phosphomolybdate:DMMP mass ratio = 1:9)

[0071] Take 0.01 mol (18.2 grams) of PMA and dissolve it in 200 mL of deionized water to form a phosphomolybdic acid solution. Then, 0.03 mol (2.8 grams) of nickel hydroxide is directly added to the phosphomolybdic acid solution, and the reaction is carried out at 60° C. for 3 hours. The impurities are filtered out, and the filtrate is rotary evaporated to obtain the product. The sample is dried in a vacuum oven at 80° C. for 12 hours to obtain nickel phosphomolybdate.

[0072] Take 5 grams of nickel phosphomolybdate and 45 grams of DMMP (nickel phosphomolybdate: DMMP = 1:9), dissolve the nickel phosphomolybdate directly in DMMP, and subject to ultrasound at 100 watts for 1 hour at room temperature. The nickel phosphomolybdate is completely dissolved in DMMP to obtain a green transparent liquid, which is a heteropolyacid compound-phosphonate liquid flame retardant (PMMPNi).

[0073] Example 8: Preparation of PMMPCu (copper phosphomolybdate:DMMP mass ratio = 1:9)

[0074] Take 0.01 mol (18.2 grams) of PMA and dissolve it in 200 mL of deionized water to form a phosphomolybdic acid solution. Then, 0.03 mol (3.0 grams) of copper hydroxide is directly added to the phosphomolybdic acid solution, and the reaction is carried out at 60°C for 3 hours. The impurities are filtered out and the filtrate is rotary evaporated to obtain the product. The sample is dried in a vacuum oven at 80°C for 12 hours to obtain copper phosphomolybdate.

[0075] Take 5 grams of copper phosphomolybdate and 45 grams of DMMP (copper phosphomolybdate: DMMP = 1:9), dissolve the copper phosphomolybdate directly in DMMP, and subject to ultrasound at 100 watts for 1 hour at room temperature. The copper phosphomolybdate is completely dissolved in DMMP to obtain a green transparent liquid, which is a heteropolyacid compound-phosphonate liquid flame retardant (PMMPCu).

[0076] Example 9: Preparation of PMMPCr (chromium phosphomolybdate:DMMP mass ratio = 1:9)

[0077] Take 0.01 mol (18.2 grams) of PMA and dissolve it in 200 mL of deionized water to form a phosphomolybdic acid solution. Then, add 0.02 mol (3.4 grams) of chromium oxide directly into the phosphomolybdic acid solution, react at 60°C for 3 hours, filter to remove impurities, and rotary evaporate the filtrate to obtain the product. Dry the sample in a vacuum oven at 80°C for 12 hours to obtain chromium phosphomolybdate.

[0078] Take 5 grams of chromium phosphomolybdate and 45 grams of DMMP (chromium phosphomolybdate: DMMP = 1:9), dissolve the chromium phosphomolybdate directly in DMMP, and subject to ultrasound at 100 watts for 1 hour at room temperature. The chromium phosphomolybdate is completely dissolved in DMMP to obtain a green transparent liquid, which is the heteropolyacid compound-phosphonic acid lipid liquid flame retardant (PMMPCr).

[0079] Application example 1: Carbon fiber reinforced epoxy resin composite material (EP / 10PM 0.5 MP 9.5 Preparation of CF

[0080] Preparation of EP / 10PM by Vacuum Assisted Resin Transfer Molding (VARTM) 0.5 MP 9.5 / CF composite materials.

[0081] Stack 10 layers of carbon fiber cloth (15×20cm) and lay them flat on the mold coated with release agent, then lay the release cloth and guide felt on the carbon fiber cloth in turn, apply sealant around the mold, lay a vacuum bag on the mold, reserve two guide ports, and connect the guide ports to the vacuum pipeline. Then seal the feed port, evacuate to ensure that the air is completely removed and the airtightness is intact, then seal the discharge port, and put the mold into a 60℃ blast oven for preheating under pressure.

[0082] 16.8 g PM 0.5 MP 9.5 Add directly to 120 grams of epoxy resin matrix, and then use mechanical stirring to mix the mixture thoroughly for 30 minutes. Use a heating jacket to heat 31.2 grams of DDM at 120°C to a molten state, and then add it to the epoxy resin mixture under continuous stirring. The mass ratio of epoxy resin matrix to DDM is maintained at 100:26. The mixture is then mechanically stirred for 30 minutes and then ultrasonically dispersed at 60°C for 30 minutes. Finally, the mixture is placed in a vacuum oven for 10 minutes to remove any embedded bubbles. The resin melt after vacuum degassing is injected into the mold cavity by vacuum suction to ensure that the resin melt fully impregnates the carbon fiber cloth. Under vacuum pressure, cure at 100°C for 2 hours and at 160°C for 3 hours. The resulting carbon fiber reinforced epoxy resin composite has a thickness of 2.5 mm.

[0083] Application Example 2

[0084] Refer to the method of Application Example 1, except that PM in step (1) 0.5 MP 9.5 PM1MP9 was used as the raw material; the other parameters and steps were kept consistent with those in Application Example 1, and finally a carbon fiber reinforced epoxy resin composite material (EP / 10PM1MP9 / CF) was prepared.

[0085] Application Example 3

[0086] Refer to the method of Application Example 1, except that PM in step (1) 0.5 MP 9.5 replaced with PM2MP8; the remaining parameters and steps were consistent with those in Application Example 1, and finally a carbon fiber reinforced epoxy resin composite material (EP / 10PM2MP8 / CF) was prepared.

[0087] Application Example 4

[0088] Refer to the method of Application Example 1, except that PM in step (1) 0.5 MP 9.5 replaced with PM4MP6; the remaining parameters and steps were consistent with those in Application Example 1, and finally a carbon fiber reinforced epoxy resin composite material (EP / 10PM4MP6 / CF) was prepared.

[0089] Application Example 5

[0090] Refer to the method of Application Example 1, except that PM in step (1) 0.5 MP 9.5 replaced with PM5MP5; the remaining parameters and steps were consistent with those in Application Example 1, and finally a carbon fiber reinforced epoxy resin composite material (EP / 10PM4MP6 / CF) was prepared.

[0091] Application Example 6

[0092] Refer to the method of Application Example 1, except that PM in step (1) 0.5 MP 9.5 replaced with PM6MP4; the remaining parameters and steps were consistent with those in Application Example 1, and finally a carbon fiber reinforced epoxy resin composite material (EP / 10PM6MP4 / CF) was prepared.

[0093] Application Example 7

[0094] Refer to the method of Application Example 1, except that PM in step (1) 0.5 MP 9.5 The remaining parameters and steps were kept consistent with those in Application Example 1, and finally a carbon fiber reinforced epoxy resin composite material (EP / 10PMMPNi / CF) was prepared.

[0095] Application Example 8

[0096] Refer to the method of Application Example 1, except that PM in step (1) 0.5 MP 9.5 The remaining parameters and steps were kept consistent with those in Application Example 1, and finally a carbon fiber reinforced epoxy resin composite material (EP / 10PMMPCu / CF) was prepared.

[0097] Application Example 9

[0098] Refer to the method of Application Example 1, except that PM in step (1) 0.5 MP 9.5 The remaining parameters and steps were kept consistent with those in Application Example 1, and finally a carbon fiber reinforced epoxy resin composite material (EP / 10PMMPCr / CF) was prepared.

[0099] Comparative Example 1: Preparation of carbon fiber reinforced epoxy resin composite material (EP / CF)

[0100] The EP / CF composites were prepared by vacuum assisted resin transfer molding (VARTM) process.

[0101] Stack 10 layers of carbon fiber cloth (15×20cm) and lay them flat on the mold coated with release agent, then lay the release cloth and guide felt on the carbon fiber cloth in turn, apply sealant around the mold, lay a vacuum bag on the mold, reserve two guide ports, and connect the guide ports to the vacuum pipeline. Then seal the feed port, evacuate to ensure that the air is completely removed and the airtightness is intact, then seal the discharge port, and put the mold into a 60℃ blast oven for preheating under pressure.

[0102] 31.2 g of DDM was heated to a molten state at 120 ° C using a heating jacket, and then added to 120 g of epoxy resin matrix under continuous stirring. The mass ratio of epoxy resin matrix to DDM was maintained at 100:26. The mixture was then mechanically stirred for 30 min and then ultrasonically dispersed at 60 ° C for 30 min. Finally, the mixture was placed in a vacuum oven for 10 min to remove any embedded bubbles. The resin melt after vacuum degassing was injected into the mold cavity by vacuum suction to ensure that the resin melt fully impregnated the carbon fiber cloth. Under vacuum pressure, it was cured at 100 ° C for 2 h and at 160 ° C for 3 h. The resulting carbon fiber reinforced epoxy resin composite material had a thickness of 2.5 mm.

[0103] Performance Testing

[0104] Cone calorimetry test and bending performance test were performed on the carbon fiber reinforced epoxy resin composite materials obtained in Application Examples 1 to 9 and Comparative Example 1. The test methods are as follows:

[0105] Cone calorimetry test: according to ISO5660 standard, sample thickness 2.5mm, surface heat flux 50kW / m 2 .

[0106] Bending performance test: Based on the standard GB / T1449-2005, the test rate is 2mm / min, the sample length is 80±2mm, the sample width is 15.0±0.2mm, the sample thickness is 2.5±0.1mm, and the sample span is 60mm.

[0107] The test results are shown in Table 2 (wherein PHRR stands for peak heat release rate, THR stands for total heat release, MARHE stands for maximum average heat release rate, and TSP stands for total smoke release).

[0108] Table 2 Performance test results of carbon fiber reinforced epoxy resin composites

[0109]

[0110] As can be seen from Table 2, compared with the comparative example, the PHRR, THR, MARHE and TSP of the composite material with flame retardant added are reduced to varying degrees. The PHRR of Application Example 4 is reduced by 40%, the MARHE is reduced by 27%, and the TSP is also reduced by 47%, showing good flame retardant and smoke suppression effects. At the same time, the addition of flame retardant does not affect the mechanical properties of the fiber composite material, but increases its bending strength and bending modulus. On the one hand, this is due to the good compatibility and uniform dispersion of liquid flame retardant in epoxy resin, and on the other hand, it is attributed to the introduction of phosphomolybdate in PM4MP6 into epoxy resin molecular segments in the form of ions. Since ionic bonds have strong interactions, the interface interaction between PM4MP6 and epoxy resin matrix is ​​enhanced.

[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A heteropolyacid compound-phosphonate liquid flame retardant, characterized in that: It is formed by the reaction of a first flame retardant and a second flame retardant; the first flame retardant is selected from phosphomolybdic acid and / or transition metal phosphomolybdate; the second flame retardant is a liquid phosphorus-based flame retardant; the mass ratio of the first flame retardant to the second flame retardant is (0.5-6): (9.5-4).

2. The heteropolyacid compound-phosphonate liquid flame retardant according to claim 1, characterized in that: The second flame retardant has a structure shown in formula (I): Wherein, R1 and R2 are each independently selected from a C1-C10 alkyl group or a C6-C20 aryl group; R3 is selected from C1-C20 alkyl, C1-C20 hydroxyalkyl, C1-C20 alkoxy or C6-C20 aryloxy.

3. The heteropolyacid compound-phosphonate liquid flame retardant according to claim 1, characterized in that: The second flame retardant is selected from one or more of dimethyl methylphosphonate, dimethyl octadecylphosphonate, dimethyl 2-(hydroxyethyl) phosphate, tributyl phosphonate and triphenyl phosphonate.

4. The heteropolyacid compound-phosphonate liquid flame retardant according to claim 1, characterized in that: The first flame retardant is selected from one or more of phosphomolybdic acid, copper phosphomolybdate, nickel phosphomolybdate and chromium phosphomolybdate.

5. The heteropolyacid compound-phosphonate liquid flame retardant according to claim 1, characterized in that: The reaction temperature is greater than room temperature; the reaction time is 1 to 6 hours.

6. A method for preparing the heteropolyacid compound-phosphonate liquid flame retardant according to any one of claims 1 to 5, characterized in that: The following steps are involved: The first flame retardant and the second flame retardant are mixed and reacted to obtain a heteropolyacid compound-phosphonate liquid flame retardant.

7. A resin composition, characterized in that The invention comprises a resin and the heteropolyacid compound-phosphonate liquid flame retardant according to any one of claims 1 to 5.

8. The resin composition according to claim 1, characterized in that The mass ratio of the resin to the heteropolyacid compound-phosphonate liquid flame retardant is (95-85):(5-15).

9. The resin composition according to claim 1, characterized in that The resin is selected from epoxy resin; the resin composition also includes an amine curing agent.

10. A flame retardant material, characterized in that: The invention comprises the heteropolyacid compound-phosphonate liquid flame retardant according to any one of claims 1 to 5 or the resin composition according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Preparation method for catalyst used for preparation of dimethyl ether through dehydration of methanol

    CN104588104A

  • Synergistic flame retardant, flame-retardant ABS composite material and preparation method of flame-retardant ABS composite material

    CN114539713A

  • Composite flame retardant as well as preparation method and application thereof

    CN116120637A

  • Ionic liquid flame retardant as well as preparation method and application thereof

    CN117510983A

  • Flame retardant phosphorus element-containing epoxy resin compositions

    US20020119317A1